2012
DOI: 10.1177/1471301212444056
|View full text |Cite
|
Sign up to set email alerts
|

Medication management: The perspectives of people with dementia and family carers

Abstract: The safe self management of medicines will be affected by the presence of dementia. A qualitative study using grounded theory was undertaken by a community nursing organisation in Melbourne, Australia, in order to develop a strength-based and person-centred approach to the assessment of medication ability. The perspectives of the person with dementia and their carers were explored to see if there were any significant differences in their medication management experiences when compared to those of older adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(185 citation statements)
references
References 21 publications
4
179
1
1
Order By: Relevance
“…This has also been reported in other research (Kaasalainen et al 2011, While et al 2012. Our evidence suggests that there are two sources of conflict.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This has also been reported in other research (Kaasalainen et al 2011, While et al 2012. Our evidence suggests that there are two sources of conflict.…”
Section: Discussionsupporting
confidence: 75%
“…The small non probability sample limits the generalizability of the study results although it is characteristic of similar qualitative studies of family caregivers of people with dementia (Kaasalainen et al 2011;While et al 2012). Despite the small sample size however, there was a consistency of findings across focus groups and individual semi-structured interviews with significant key findings relevant to the research question identified.…”
Section: Limitationsmentioning
confidence: 76%
See 2 more Smart Citations
“…If a family member makes an error they have all the burden of responsibility that a professional bears combined with the terrible experience of harming someone close to them. Interviews with carers suggest that the responsibility for giving powerful medications can become burdensome both because of the time commitment and anxiety about making mistakes; many carers do not receive clear guidance about medication, leading to omissions, incorrect doses, anxiety and confusion which are often not recognised by health professionals (While et al 2013 ). Relatives of people near the end of their lives face the additional worry about hastening death through improper use of medication (Payne et al 2014 ).…”
Section: The Responsibilities Of Carersmentioning
confidence: 99%